Theodore Finch’s Social Conflict in All the Bright Places by Jennifer Niven - Abu Fanani (STKIP PGRI Lubuklinggau, 2022)
This article aimed at analyzing the social conflict of Theodore Finch in All the Bright Places Novel by Jennifer Niven. This study focused on the main character, Theodore Finch. Finch is a man fascinated by death. This study used a descriptive qualitative method for analyzing the data. In this study, the theories the researcher uses were social conflict by Lewis, cause of conflict by Mike, and New Criticism Theory. This method was applied to analyze the main character's conflict in society and his cause of conflict, and how he solved the conflict. The finding was that Finch underwent social conflicts: conflict of position, conflict of interest, and conflict of role, whilst, cause of conflict refers to the difference in perception and difference in personality. The last was Finch’s problem solving: being patient, being careful in behavior, and being casual and normal.